Study characteristic of oil-water emulsion fuel for diesel engine - Muhammad 'Ammar Shakir, Ishar (2011)
This report deals with propose of new oil-water emulsion fuel mixtures which are to be improved by manipulating the percentage of oil and water added in the mixer. The objective of this project is to analysis the characteristic of the emulsion fuels produced by using laboratory analysis. The vertical mixer is used in this research. Emulsified fuels would be one of the best alternatives to replace the current fuel in the future. In order to produce the desired emulsion fuels, the mixer need to be designed and set up. After the emulsion fuels are produced, the mixture is later on be analysis using laboratory analysis such as ball-falling viscometer and oxygen bomb calorimeter. Data and results of the experiment are observed and recorded. The obtained data indicated that the emulsion fuel with 30% of water added shows the most stable physical characteristic. By the end of the report, the emulsion fuels where able to be produced by the mixer and the mixtures produced can be analysis.